Estimating the Determinants of Remittances Originating from U.S. Households using CPS Data - Nicole B. Simpson; Chad Sparber (Institute of Labor Economics (IZA), 2019)
The U.S. is the largest source country of remittances with an outflow of more than 70 billion estimated for 2016 (according to data from the World Bank). This paper is the first to use Current Population Survey (CPS) data to estimate the determinants of remittances originating from the United States for a diverse set of approximately 3,800 households with at least one foreign-born worker. We employ a gravity model examining the role of various push, pull, and distance factors. Most notably, higher household earnings push monetary transfers abroad: We estimate an average earnings elasticity in the range of 0.20-0.30. Remittances are more responsive to earnings in households with more adult women relative to men.
Keywords: F24; J61; 330; immigration; remittances